2018
DOI: 10.3389/fonc.2018.00536
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Differences and Lung Cancer Survival—Systematic Review and Meta-Analysis

Abstract: Background: The impact of socioeconomic differences on cancer survival has been investigated for several cancer types showing lower cancer survival in patients from lower socioeconomic groups. However, little is known about the relation between the strength of association and the level of adjustment and level of aggregation of the socioeconomic status measure. Here, we conduct the first systematic review and meta-analysis on the association of individual and area-based measures of socioeconomic status with lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
58
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 122 publications
(356 reference statements)
11
58
1
2
Order By: Relevance
“…Two‐year all‐cause mortality of ever‐smokers was significantly higher than that of never‐smokers, consistent with this cohort study 46 . Studies reporting an association between reduced lung cancer survival and low individual income and area‐level SES in the meta‐analysis did not adjust for relevant prognostic factors like smoking 47,48 . Even after controlling for underlying prognostic factors, there was still some contextual effect of area‐level deprivation found in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Two‐year all‐cause mortality of ever‐smokers was significantly higher than that of never‐smokers, consistent with this cohort study 46 . Studies reporting an association between reduced lung cancer survival and low individual income and area‐level SES in the meta‐analysis did not adjust for relevant prognostic factors like smoking 47,48 . Even after controlling for underlying prognostic factors, there was still some contextual effect of area‐level deprivation found in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, within oncology a small number of studies have examined the relative effects of individual-level and ecological-level deprivation on both cancer risk [14][15][16] and outcomes. [17][18][19] Generally, these studies have quantified independent effects of both individual and ecological deprivation, and for both, more deprived areas or individuals have higher risk and lower survival. 14 17-19 However, the strength and nature of these trends varies considerably across factors including sex, level of geographical aggregation and which type of deprivation metric is used.…”
mentioning
confidence: 99%
“…14 17-19 However, the strength and nature of these trends varies considerably across factors including sex, level of geographical aggregation and which type of deprivation metric is used. 18 Furthermore, these associations are not well understood in a UK context, especially in terms of making use of recent data, and an improved understanding will be important in order to reduce inequalities as part of the National Health Service (NHS) long-term plan for 2020 to 2030. 20 The research on health inequalities on which the NHS long-term plan is based uses data aggregated to small area level, and so improving our understanding of how reliably this matches individual-level circumstances is important in terms of developing further policies which more specifically target individual-level variation in health outcomes.…”
mentioning
confidence: 99%
“…The two-year overall survival rate is 20-40% in LD and 5 % for ED [4]. Several studies have described an association between socioeconomic status and the risks of developing Non-Small Cell Lung Cancer (NSCLC) [5,6]. A previous Swedish study based on a regional cohort of NSCLC patients found evidence of socioeconomic gradients in diagnostic intensity, choice of treatment and outcomes [7].…”
Section: Introductionmentioning
confidence: 99%